1995
DOI: 10.1099/0022-1317-76-7-1719
|View full text |Cite
|
Sign up to set email alerts
|

N1 neuraminidase of influenza virus A/FPV/Rostock/34 has haemadsorbing activity

Abstract: The neuraminidase (NA) gene of influenza virus A/FPV/ Rostock/34 virus (H7N1) was cloned and expressed in Sf9 cells using a baculovirus vector. The expression product had the expected molecular mass and showed neuraminidase activity. NA expressed in St9 cells also showed haemagglutinating activity as indicated by its ability to induce haemadsorption of chicken red blood cells. Haemadsorption depended on the presence of neuraminic acid on the erythrocytes, but was not blocked by 2-deoxy-2,3-dehydro-N-acetylneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…This site bears no resemblance to either the NA active site or the HA sialic acid binding site, and indeed the specificity of binding is unlike that of HA, in that the bound sialic acid is not released by N9 or N2 NA activity but only by bacterial sialidases of very broad specificity 60 . HB activity was also found in the N1 NA of fowl plague virus 61 . Comparisons of sequences in the area of the second binding site suggested that avian viruses have the HB activity while human viruses do not 59,61,62 , but so far a specific function of the HB activity in bird viruses has not been established.…”
Section: Some Nas Have a Second Sialic Acid Binding Sitementioning
confidence: 87%
“…This site bears no resemblance to either the NA active site or the HA sialic acid binding site, and indeed the specificity of binding is unlike that of HA, in that the bound sialic acid is not released by N9 or N2 NA activity but only by bacterial sialidases of very broad specificity 60 . HB activity was also found in the N1 NA of fowl plague virus 61 . Comparisons of sequences in the area of the second binding site suggested that avian viruses have the HB activity while human viruses do not 59,61,62 , but so far a specific function of the HB activity in bird viruses has not been established.…”
Section: Some Nas Have a Second Sialic Acid Binding Sitementioning
confidence: 87%
“…Another potential role of NA was suggested in that it may permit transport of the virus through the mucin layer present in the respiratory tract, facilitating the virus interaction with the target epithelial cells. Some NA (N1 and N9 subtypes) have both a receptor-binding site and a NA active site [43,44]. However, the receptor speci®city and function of this receptor-binding activity is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, residue 151, unlike residue 150, is categorized as a catalytic site residue and is believed to stabilize the transition state intermediate [26]. The position of these residues in or close to the catalytic site and the inhibition of NAmediated binding by oseltamivir suggest that the binding of NA to turkey erythrocytes is mediated via the catalytic site and not via haemadsorption sites, which are secondary sialic acid-binding sites that have been described for some avian NAs [27][28][29][30][31]. At the moment it is not clear what mechanism is involved in the 150HR-mediated binding of erythrocytes and what functional changes are caused in NA by this amino acid substitution.…”
Section: Discussionmentioning
confidence: 99%